COMPARATIVE ANALYSIS OF FINANCIAL INDEPENDENCE IN ACEH PROVINCE (Period 2015-2020) - Saharuddin; Febricha Sirma Chania; Cut Muftia Keumala; Khairil Anwar; Rico Nur Ilham (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
This research aims to determine regional financial independence and a comparison of regional financial independence in the 5 parent Regency Governments and 5 expansion Regency/Cities in Aceh Province in 2015-2020. The data analysis methods used are Descriptive Statistical Tests and Comparative Tests. The results of the research show that: the regional financial independence of North Aceh Regency in 2015, 2017 and 2019-2020 is included in the instructive relationship pattern, while in 2016 and 2018 it is included in the instructive relationship pattern. consultative relationship. Lhokseumawe City, South Aceh Regency, Aceh Singkil Regency, Bener Meriah Regency, East Aceh Regency and Pidie Jaya Regency from 2015-2020 are included in the instructive relationship pattern. The level of regional financial independence in Central Aceh Regency from 2015-2018 and 2020 is included in the consultative relationship pattern. Langsa City from 2015-2017 and 2019 is included in the instructive relationship pattern. Meanwhile, in 2018 and 2020 it is included in the consultative relationship pattern. The level of regional financial independence of Pidie Regency from 2015-2017 and 2019-2020 is included in the instructive relationship pattern and in 2018 it is included in the consultative relationship pattern. Comparison of the regional financial independence of North Aceh Regency and Lhokseumawe City, there is no significant difference. There is no significant difference in the comparison of regional financial independence for the 2015-2020 period between South Aceh Regency and Aceh Singkil Regency. There is a significant difference in the comparison of regional financial independence between Central Aceh Regency and Bener Meriah Regency for the 2015-2020 period. There is a significant difference in the comparison of regional financial independence in East Aceh Regency and Langsa City for the 2015-2020 period. There is no significant difference in the comparison of regional financial independence for the 2015-2020 period between Pidie Regency and Pidie Jaya Regency.